Empowering Technical Skills and Soft Skills in Software Engineering Students through Problem-Based Learning - Oran, Ana Carolina; Lima, Rayfran Roca; Gadelha, Bruno; Maia, Nayane; Silva, Williamson; Rivero, Luis (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
CONTEXT: The software industry has been increasing its employees’ demands regarding technical, behavioral, and social skills. Therefore, software engineering courses must exceed the limits of theory and academic examples, providing students with practical experiences to prepare them for the challenges they will encounter in real projects. OBJECTIVE: This paper aims to present the results of applying the Problem-Based Learning (PBL) methodology in the teaching of the Practice in Software Engineering (PSE) discipline integrated with the Verification, Validation, and Testing (VV&T) discipline. METHOD: During one semester, divided into five multidisciplinary teams, PSE and VV&T students developed five real web systems experiencing software engineering practices (elicitation, analysis and design, coding and testing, deployment) and entrepreneurship practices (elaboration and pitch presentation to investors). At the end of the semester, we surveyed to collect students’ opinions about their level of learning, satisfaction with project development, knowledge related to integrating complementary content, and the experience acquired with the discipline. RESULTS: The results show evidence of the effectiveness of applying the PBL methodology in the learning and experience acquired by the students of the PSE and VV&T disciplines. The results went beyond the classroom’s limits, directly impacting the students’ careers. CONCLUSION: Developing real projects with real clients, deadlines, and constraints, proved to be a fundamental element in the development of technical knowledge (technical skills) and behavioral skills (soft skills), increasing the student’s confidence level and enabling them to act in software engineering disciplines.